Understanding the causes, factors, and methods of reducing students' exam anxiety in high school exams - Akram Hafezi; Samira Etemadi (Journal of Social, Humanity, and Education, 2022)
Purpose: The purpose of this study was to identify the causes, factors, and methods to reduce students' exam anxiety in high school exams. Research methodology: In order to conduct this research, from among the students of district one of Rey city and from among 690 seventh grade female students, 100 of them were selected by using a non-random sampling method. The questions in the questionnaire consisted of 21 closed-ended questions and 1 open-ended question. Results: The findings indicate that several factors are effective in aggravating test anxiety. Losing a privileged academic position in the classroom followed by personality impairment disturbs the student's peace of mind and causes students to become anxious during the exam. Limitations: In addition to the factors mentioned as the causes of test anxiety, there may be other factors in these fields that can affect such as hereditary factors, weakness of personality, weakness of faith, and other cases that cannot be measured or not mentioned in this study. Contribution: This study is expected can give a piece of knowledge about the factors that can cause anxiety during exams to students and the method to reduce it.